MMS22L Expression as a Predictive Biomarker for the Efficacy of Neoadjuvant Chemoradiotherapy in Oesophageal Squamous Cell Carcinoma - Luo, Qiyu; He, Wenwu; Mao, Tianqin; Leng, Xuefeng; Wu, Hong; Li, Wen; Deng, Xuyang; Zhao, Tingci; Shi, Ming; Xu, Chuan; Han, Yongtao (Frontiers in Oncology, 2021)
Long-term survival in oesophageal squamous cell carcinoma (ESCC) is related with pathological response after neoadjuvant chemoradiotherapy (NCRT) followed by surgery. However, effective biomarkers to predict the pathologic response are still lacking. Therefore, a systematic analysis focusing on genes associated with the efficacy of chemoradiotherapy in ESCC will provide valuable insights into the regulation of molecular processes. By screening publications deposited in PubMed, we collected genes associated with the efficacy of chemoradiotherapy. A specific subnetwork was constructed using the Steiner minimum tree algorithm. Survival analysis in Kaplan-Meier Plotter online resources was performed to explore the relationship between gene mRNA expression and the prognosis of patients with ESCC. Quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting, and immunohistochemical staining (IHC) were used to evaluate the expression of key genes in cell lines and human samples. The areas under the receiver operating characteristic (ROC) curves (AUCs) were used to describe performance and accuracy. Transwell assays assessed cell migration, and cell viability was detected using the Cytotoxicity Assay. Finally, we identified 101 genes associated with efficacy of chemoradiotherapy. Additionally, specific molecular networks included some potential related genes, such as CUL3, MUC13, MMS22L, MME, UBC, VAPA, CYP1B1, and UGDH. The MMS22L mRNA expression level showed the most significant association with the ESCC patient outcome (p < 0.01). Furthermore, MMS22L was downregulated at both the mRNA (p < 0.001) and protein levels in tumour tissues compared with that in normal tissues. Lymph node metastasis was significantly associated with low MMS22L expression (p < 0.01). MMS22L levels were inversely correlated with the NCRT response in ESCC (p < 0.01). The resulting area under the ROC curve was 0.847 (95% CI: 0.7232 to 0.9703; p < 0.01). In conclusion, low expression of MMS22L is associated with poor response to NCRT, worse survival, lymph node metastasis, and enhanced migration of tumour cells in ESCC.